Chemical treatment of the intra-canal dentin surface: a new approach to modify dentin hydrophobicity - Cesar GAITAN-FONSECA; Pierre-Yves COLLART-DUTILLEUL; Vincent SEMETEY; Olivier ROMIEU; Roel CRUZ; Hector FLORES; Frederic CUISINIER; Elias PEREZ; Amaury POZOS-GUILLEN (Journal of Applied Oral Science, 2013)
Objective This study evaluated the hydrophobicity of dentin surfaces that were modified through chemical silanization with octadecyltrichlorosilane (OTS). Material and Methods An in vitro experimental study was performed using 40 human permanent incisors that were divided into the following two groups: non-silanized and silanized. The specimens were pretreated and chemically modified with OTS. After the chemical modification, the dentin hydrophobicity was examined using a water contact angle measurement (WCA). The effectiveness of the modification of hydrophobicity was verified by the fluid permeability test (FPT). Results and Conclusions Statistically significant differences were found in the values of WCA and FPT between the two groups. After silanization, the hydrophobic intraradicular dentin surface exhibited in vitro properties that limit fluid penetration into the sealed root canal. This chemical treatment is a new approach for improving the sealing of the root canal system.